Integration of congenital cytomegalovirus screening within a newborn hearing screening programme. (27th March 2019) - Beswick, Rachael; David, Michael; Higashi, Hideki; Thomas, Delene; Nourse, Clare; Koh, Guan; Koorts, Pieter; Jardine, Luke A; Clark, Julia E
Abstract : Aim: Targeted screening by a salivary cytomegalovirus (CMV) polymerase chain reaction (PCR) of infants who 'refer' on their newborn hearing screen has been suggested as an easy, reliable and cost‐effective approach to identify and treat babies with congenital CMV (cCMV) to improve hearing outcomes. This study aimed to investigate the feasibility and cost‐effectiveness of introducing targeted salivary cCMV testing into a newborn hearing screening programme. Methods: The study included three tertiary maternity hospitals in Queensland, Australia between August 2014 and April 2016. Infants who 'referred' on the newborn hearing screen were offered a salivary swab for CMV PCR at the point of referral to audiology. Swabs were routinely processed and tested for CMV DNA by real‐time quantitative PCR. Parents of babies with a positive CMV PCR were notified, and the babies were medically assessed and, where appropriate, were offered treatment (oral valganciclovir). Results: Of eligible infants, the parents of 83.0% (234/283) consented to the cCMV screen. Of these, 96.6% returned a negative result (226/234), and 3.4% (8/234) returned a positive result (three true positive; five false positive). The prevalence of cCMV for infants with confirmed hearing loss was 3.64% ( P = 2/55; confidence interval = 0.44–12.53%). The cost comparison suggests the cost implementation of cCMV screening (and subsequent potential treatment benefits and management over time), compared to non‐screening (and subsequent management), to be negligible. Conclusion: Incorporating cCMV testing into Universal Newborn Hearing Screening within Queensland is realistic and achievable, both practically and financially.